(untitled) (Jurnal Ipteks Terapan, 2023)
There are 322 million people suffering from depression globally, compared to other situations, the likelihood of stress during pregnancy and postpartum is potentially higher. The prevalence of postnatal depression is around 13% worldwide, affecting around 10%-15% of women in developed countries and affecting around 20% of women in developing countries. Postpartum depression is a moderate to severe mood disorder that occurs during the perinatal period. There is a need for preventive care to prevent postpartum depression in mothers, one way of preventing this is by providing support from the husband in accompanying postpartum mothers. The aim of this research is to review several research results related to the husband’s role in preventing postpartum depression using a System Literature Review design . So, based on the articles obtained, an in-depth analysis will be carried out on how husbands play an important role which will greatly influence the mental health of postpartum mothers. The findings show that there is an inversion in the level of support given by the husband and the occurrence of postpartum depression.